Efetividade de diferentes agentes dessensibilizantes no clareamento dental de consultório– uma revisão sistemática e meta-análise - Fachin, Felipe Gustavo (2022)
To summarize the available evidence on the effectiveness of desensitizing agents on dentinal sensitivity resulting from tooth whitening. Sources: On September 4, 2021, a comprehensive search was performed on MEDLINE via PubMed, EMBASE, LILACS (Latin American and Caribbean Health Science Literature), LIVIVO, SCOPUS, Web of Science, and in the gray literature by Google Scholar. Study selection: After removal of duplicates, title and abstract screening by two reviewers (performed in the Rayyan tool for systematic reviews), 13 articles were included, selected only blinded randomized clinical trials, which present patients with discolored teeth undergoing tooth whitening performed in the office and/or at home and desensitizing agents used. Data were collected from authors, year of publication, objectives or research questions, desensitizer, number of participants, number of groups, description of the control group, description of the study group, bleaching approach, evaluated outcomes, main results, main conclusions, scale used to measure the outcome, risk of tooth sensitivity (result), statistical test used, odds ratio/CI results, analysis of intensity of dentin sensitivity (intergroup statistical test), analysis of intensity of dentin sensitivity (intragroup statistical test ) and maximum analysis time. Conclusion: In the findings reported in this study, it was possible to verify that the desensitizing agents would significantly affect tooth sensitivity and the oddsratio of patients admitted to whitening of admitted patients.